Student Engagement in Distance-based Vocational Education - Anne Yates; Wendy Brindley-Richards; Tony Thistoll (Flexible Learning Association of New Zealand, 2014)
Students enrolled in distance education courses tend to have lower course completion rates than those who attend face-to-face classes (Simpson, 2013). This article reports on a collective case study undertaken at a vocational, distance education provider in New Zealand, whose course completion rates have risen over recent years to match those of similar face-to-face institutions. This research investigated institutional factors that have contributed towards this improvement, from the perspectives of the staff involved. Results show staff believe there are key enablers and barriers to student engagement and course completion, but the barriers are not insurmountable. The implication is that distance education providers can improve student engagement and completion rates through effective interventions.